ПІВДЕННОУКРАЇНСЬКЕ КОЗАЦТВО І КРИМСЬКА ВІЙНА (Zaporizhzhia Historical Review, 2021)
The author studies the role of Southern Ukraine Cossacks in the Crimean War. The activities of Azov Cossacks in the war are described in details. The politics of Russian government concerning the Cossacks in the Southern Ukraine after Crimean War are analyzed in the article.